Pengaruh Wadah dan Lama Penyimpanan terhadap Kualitas Fisik dan Jumlah Bakteri Susu Sapi Friesian Holstein di Benlutu - Novita Teme; Stefanus Sio; Theresia I. Purwantiningsih (JAS, 2021)
This research was conducted at the Chemical Laboratory of Widya Mandira University, Kupang from December 4 to December 22, 2018. This study aims to determine the physical quality of Friesian Holstein cow's milk and the total number of bacteria in each type of container and different storage time and can provide information to the community regarding the type of container and storage time for fresh milk is good so that the quality and quality of the milk is maintained. In this study, fresh milk was used with different storage containers made from glass, plastic and commercial plastic. The experimental design used was a factorial completely randomized design with 4 x 3 treatments and 4 replications. The treatments consisted of W0 = a container made of glass, W1 = a container made of plastic, and W2 = a container made of Tupperware which was stored for 1 day (P0), 3 days (P1), 5 days (P2), and 7 days (P3). The variables observed were an organoleptic test, acidity titration, pH, and TPC test. The results of the ANOVA variety showed that the storage container and storage time had a very significant effect (P <0.05) on the degree of acidity by tetrimetric, pH, and TPC, the interaction of storage containers, and storage time on the degree of acidity and TPC was very significant (P <0, 05) but the interaction for pH was not significant (P> 0.05). The conclusion from this study is that the type of container made from plastic bottles with a storage time of 1 day is better than containers made from glass bottles and tupperware. This can be seen from the results of the organoleptic test, acidity titration, pH, and TPC test.